Development of analysis of volatile polyfluorinated alkyl substances in indoor air using thermal desorption-gas chromatography–mass spectrometry - Wu, Yaoxing (2013)
The study attempts to utilize thermal desorption (TD) coupled with gas chromatography–mass spectrometry (GC–MS) for determination of indoor airborne volatile polyfluorinated alkyl substances (PFASs), including four fluorinated alcohols (FTOHs), two fluorooctane sulfonamides (FOSAs), and two fluorooctane sulfonamidoethanols (FOSEs). Standard stainless steel tubes of Tenax/Carbograph 1 TD were employed for low-volume sampling and exhibited minimal breakthrough of target analytes in sample collection. The method recoveries were in the range of 88–119% for FTOHs, 86–138% for FOSAs, exhibiting significant improvement compared with other existing air sampling methods. However, the widely reported high method recoveries of FOSEs were also observed (139–210%), which was probably due to the structural differences between FOSEs and internal standards. Method detection limit, repeatability, linearity, and accuracy were reported as well. The approach has been successfully applied to routine quantification of targeted PFASs in indoor environment of Singapore. The significantly shorter sampling time enabled the observation of variations of concentrations of targeted PFASs within different periods of a day, with higher concentration levels at night while ventilation systems were shut off. This indicated the existence of indoor sources and the importance of building ventilation and air conditioning system.